2023
DOI: 10.3390/jmse11061200
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Analysis of Fire Resistance for Bulkhead and Deck Structures of Ships and Offshore Installations

Abstract: Investigating the loss of integrity (E) in cabin walls and decks, as well as the role of insulation capabilities, holds significant implications for preventing serious human, economic and environmental damage caused by the ignition of cabins in ships and ocean platforms due to fires and explosions. In this study, the fire resistance of A-60 class ship bulkheads and decks was evaluated through two groups of standard fire resistance tests. In the first test, the steel structure side of the bulkhead was exposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The arrangement of ventilation conditions in the ship engine room has a great effect on flammable material ignition and flame propagation, which affects the combustion characteristics in ship fire accidents [26]. Numerical models for ship fires were built by CFD-based tools based on standards and cases [27,28], which showed better improvements by combating with experimental data [29,30]. In another experiment, it was found that the general behavior of marine oils was steady combustion after ignition in open space, where the low and intermediate fractions began to evaporate, causing a large number of bubbles [31].…”
Section: Introductionmentioning
confidence: 99%
“…The arrangement of ventilation conditions in the ship engine room has a great effect on flammable material ignition and flame propagation, which affects the combustion characteristics in ship fire accidents [26]. Numerical models for ship fires were built by CFD-based tools based on standards and cases [27,28], which showed better improvements by combating with experimental data [29,30]. In another experiment, it was found that the general behavior of marine oils was steady combustion after ignition in open space, where the low and intermediate fractions began to evaporate, causing a large number of bubbles [31].…”
Section: Introductionmentioning
confidence: 99%